(3GdeY`H``hOGJ GdoeS`JM`OKI aj eU``Q Gdb`Oje`I MJi fg``GjI YU``hQ GdOhd`I GdM`OjKI (B/s - (3,eUWai eMe`hO YHO GdQMef CMe`Os; (3CM`e`O eMe`hOYj`S`is; (3MS``f fUQ GdOjfs (2024)
(3GdeYHhOGJ GdoeSJMOKI aj eUQ GdbOjeI MJit fgGjI YoUhQ GdOhdI GdMOjKI, hJe JbSjegG Edit(B: ((3ebOeI, hCQHYI aUhd, hNGJeI(B)(3, hJfGhdJ GdebOeI ETcGdjI GdHMK, hGdefgL GdYdej GdPj GJHYg GdHGMK, hGdaUhd(B- (3cd aUd jJchf ef SJI YfGUQ QFjSjI oJSHb HJegjO(B-(3, GdaUd GdChd GdeYHhOI (B"(3ehJ(B"(3, hGdaUd GdKGfj GdeYHhOI (B"(3hGSJ(B"(3, hGdaUd GdKGdK eYHhO GdYeGQfI (B"(3CJhf(B"(3, hCNjkQG GdaUd GdQGHY GdeYHhOI (B"(3QYJ JGhj(B"(3, hgPg GdaUhd ef GdOQGSI oJM`Ghd GdELGHI Ydit(B: (3CSHGH GdGSJMOGK dJdc GdeYHhOGJ hcjajI GSJMOGKgG hUjGZJgG ef MjoK (B((3GdpacQI, GdeVehf GdQeRj, GdTcd GdJUhjQj(B)(3, hJdj GdaUhd NGJeI JJVef Cge GdfJGFL GdJj JhUd EdjgG GdHGMK ef NdGd GdOQGSI(B.s
Synthetic Gods in Ancient Egypt till the End of the New Kingdom.(3y (BIt was divided into: an Introduction, and four chapters reviewing: (the Goddess (3z(BMut,(3y (Bthe Goddess (3z(BWaset,(3y (Bthe Amarna divinity (3z(BAton,(3y (Band the goddess (3z(BRaettawy(3y(B). These chapters attempted to answer the reasons for the creation of these deities and how they were created and formulated in terms of: Idea, symbolic Significance and Pictorial Form. The Conclusion reviewed the results that the researcher.s
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B196-209.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdMVGQI GdaQYhfjIs; (3bOeGA GdeUQjjfs; (3Cehfs -- (3ehJs -- (3ehfJhs